How to manage stress for success - Geber, Sara Zeff (American Management Association New YorkUS, 1996)
Provides a general understanding of stress. Examines issues including: sources of stress; psychological responses to stress; indicators of stress overload; eliminating or reducing stress; and, adding and increasing coping mechanisms.